The Emptiness of Asia - Harrison, Thomas.
1 online resource (194 pages)
Keywords: Aeschylus' “Persions“ is the first surviving Greek drama. This book provides aims to provide both a more satisfactory reading of the “Persians“ and a richer picture of fifth-century history - the history both of events and ideology.